Characterization of fracture behavior of a Ti alloyed supermartensitic 12%Cr stainless steel using Charpy instrumented impact tests. (December 2017) - Tavares, S.S.M.; Silva, M.B.; de Macêdo, M.C.S.; Strohaecker, T.R.; Costa, V.M.
Abstract: In this work, the toughness of a Ti-alloyed supermartensitic stainless steel with 12%Cr was evaluated by instrumented Charpy impact tests at − 46 °C. The material was heat treated by quenching and tempering at 500 °C or 650 °C. The temper embrittlement phenomena was detected in the specimen tempered at 500 °C, while the specimens as quenched and quenched and tempered at 650 °C presented a ductile fracture with high impact energy values. The predominance of cleavage fracture instead of intergranular cracks suggests that the temper embrittlement was caused by fine and disperse precipitation observed in the specimen tempered at 500 °C. The dynamic initiation fracture toughness (JId ) was calculated from the force versus deflection curves using three different methods suggested in the literature to obtain the initiation energy. Highlights: 12%Cr SMSS tempered at 500 °C shows temper embrittlement at − 46 °C. 12%Cr SMSS tempered at 650 °C shows high toughness and ductile behavior at − 46 °C. Temper embrittlement of 12%Cr SMSS is related to fine and disperse precipitation. Instrumented Charpy test was used to obtain the dynamic initiation fracture toughness of SMSS.